Dual convergence approach: A two way approach to the design of matched converter-motor pair for asynchronous drives. Part II: Experimental validation of the approach and performance of the machine - Singh G.K.; Bhattacharyya M. (My University, 2025)
Dual Convergence Approach (DCA) - a two way approach to the design of converter-motor pair for asynchronous drives is unique as it contemplates a gainful use of the till-believed undesirable time-harmonics in the supply system for production of aiding torque through interactive effects of space-harmonics deliberately introduced in conductor distribution through careful design of the windings. The theoretical description of the approach is given in details, in companion paper. This paper presents experimental validation of the approach and detailed performance analysis of the machine with symmetrized winding designed by DCA and operating on nonsinusoidal supply.